Improved pulse high frequency voltage injection method based low-speed sensorless control of axial field flux-switching permanent magnet motors - Zhang, Wei; Tai, Ziyi; Jin, Huayang; Guo, Yongzheng; Liang, Xingyan (JOURNAL OF POWER ELECTRONICS, 2025)
To enhance the operating performance of the axial field flux-switching permanent magnet motor (AFFSPMM) at low speeds and minimize the rotor position inaccuracies produced by the digital filters in the conventional pulse high frequency voltage injection method (PHFVIM), an improved PHFVIM is proposed in this paper. First, a double-second-order general integrator (DSOGI) is developed to replace the traditional band-pass filter (BPF) and low-pass filter (LPF), providing a more accurate extraction of the high-frequency response current in the q-axis and the position error signal. Then a PIR controller is developed to replace the traditional PI controller, effectively tracking the high-frequency response current. Additionally, both simulations and experiments have been conducted to validate the viability and effectiveness of the improved sensorless control method for AFFSPMMs. Results demonstrate that the improved PHFVIM significantly reduces the delays associated with digital filter signal processing, decreases the computational load, and increases the precision of the control system.